O canto e a música no contexto ritual da liturgia na igreja católica: desafios para a formação de agentes na diocese de Vacaria/RS - Zanandrea, Rene Antonio (2009)
Song and music in the ritual context of the liturgy in the Catholic Church: challenges for the formation of agents in the Diocese of Vacaria/RS. The sounds of nature, selected and combined, gave origin to the musical art. Music belongs to human culture; it is constitutive of its own existence. In the approach of this topic, the first chapter of this work looks for a historical approach to music. It investigates the anthropology of music and its ritual relation to the sacred, also as a part of Christian rites. The II Vatican Council has restored, in the Catholic Church, the value of musical art and increased its possibilities. The musical art begins to be inserted into the sacramental rites. More than singing in the liturgy, there is the need to sing liturgy itself. Music begins to be understood as a means of participation, helping the faithful to express their faith, their gratitude and their needs. In the second part, one looks for an approach to the liturgical-musical reality of the Diocese of Vacaria/RS. Besides the historical-geographical localization, there appear significant elements obtained through a field research. Having as a referencial point the Course of Liturgical and Pastoral Singing (Curso de Canto Litúrgico e Pastoral =CCLP), since three years in function, one tries to perceive what understanding persons have of music and the form by which it influences their lives. Afterwards, the research tries to capture the function of ritual music in liturgy in the opinion of the persons interviewed. In a general way, the persons interviewed show their understanding that a well-song celebration animates the journey and makes the Christian Church to be alive. There is, therefore, the need to prepare the agents of musical art, in order that they contribute to perform living celebrations through an appropriate use of music and song in the liturgical celebrations. The third chapter of the present work tries to point out practical indications for the formation of ministers of song and music, as well as for acting in liturgical rites. Such indications take into consideration the steps which already became reality since the conciliar renewal, especially the reflections and requirements necessary for the evangelizing action from the point of view of the Theology of Liberation. This way of reflecting and making theology has inspired significant steps in the biblical reinterpretation and continues to offer methods of pastoral analysis and reflection, including liturgical ones. To the agents of song and musical ritual of the Diocese of Vacaria/RS, it is suggested to act by taking into consideration the faithful as subjects of the liturgical action, offering them active participation and moments of true communication with their Creator, through wellsong liturgies. The suggestion is the continued and progressive formation on various levels, counting on the collaboration of the subjects of this process, namely, the agents themselves.